Tectonic significance of the Cretaceous granitoids along the south‐east coast of continental China. (14th December 2018) - Xue, Qiqi; Niu, Yaoling; Chen, Shuo; Sun, Pu; Duan, Meng; Gao, Yajie; Hong, Di; Xiao, Yuanyuan; Wang, Xiaohong; Guo, Pengyuan
Abstract : We present the results of our study on 16 Cretaceous granitoid plutons along the south‐east coast of continental China. The zircon U–Pb ages and the bulk‐rock Rb–Sr isochron age ( R 2 = 0.935) indicate that the granitoids represent the last episode of magmatism (119–92 Ma) associated with the paleo‐Pacific Plate subduction beneath continental China. These granitoids show large compositional variation that is to a first‐order consistent with varying extents of magma evolution, which is best expressed by a large SiO2 /MgO range and correlated trends of SiO2 /MgO with the abundances and ratios of major and trace elements. The correlated Nd (εNd(t) = −6.1 to −1.2) and Hf (εHf(t) = −4.7 to +3.4) isotopic variation reflects parental magma compositional differences as a result of varying sources and processes. The Nd–Hf isotope data indicate that these granitoids were produced by mature continental crust melting with significant mantle input ( 20–60%). Rhyolite‐MELTS modelling shows that relative to the less evolved (i.e., low SiO2 /MgO) granitoid plutons, the progressively more evolved (i.e., varying larger SiO2 /MgO) plutons can be explained by varying extents ( 24% to 67%) of fractional crystallization. The origin of the magmas parental to the granitoids is best explained by a two‐stage process: (a) subducting slab dehydration‐induced mantle wedge melting for basaltic magmas and (b) ascent and underplating/intrusion of the basaltic magmas caused the mature crustal melting for the granitoid magmas. The systematic northward decrease in εNd(t) and εHf(t) suggests progressively more enriched crustal material towards the north, but it may very well indicate northward crustal thickening, permitting a greater extent of crustal assimilation.